PENGARUH MODEL PEMBELAJARAN BERDASARKAN MASALAH (PBM) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - rina sailifa; tri jalmo; rini rita marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Based on interview with biology teacher in SMP N 22 Bandar Lampung, student’s critical thinking skill were not optimally developed. Alternative that can be used to improve student’s critical thinking is problem based learning (PBL) model. This experiment aims to find out the influence of PBLmodel towards improvement of student’s critical thinking skill. This is quasi experiment using pretest posttest group non equivalent design. Sample are students from VIIIA and VIII B  which selected from population by random sampling method. Quantitative data from the average of pretest, posttest and N-gain which statistically analyzed with Mann Whitney-U test. Qualitative data are student’s critical thinking skilldescription, learning activities and student’s response about applicating PBL model which descriptively analyzed. Result of this experiment showed that student’s critical thinking skill improved significantly in giving reason (18,34%) and giving solution (44,36%)whereas not in formulating problem, hypothesize and interpretating statement.The student’s learning activities in all observed aspects (78,49%).  Student’s learning activities improved in asking question (6,4%)and presenting group discussion result (16,45%) which are at high level. The students (86,25%)  also give positive response in PBL.  Keywords:  problem based learning model, critical thinking skill, human digestive system